Molecular spectroscopy in a solid-state device. Issue 8 (7th May 2019) - Atxabal, Ainhoa; Arnold, Thorsten; Parui, Subir; Zuccatti, Elisabetta; Cinchetti, Mirko; Casanova, Fèlix; Ortmann, Frank; Hueso, Luis E.
Abstract : The quantification of the electronic transport energy gap of a molecular semiconductor is essential for pursuing any challenge in molecular optoelectronics. Abstract : The quantification of the electronic transport energy gap of a molecular semiconductor is essential for pursuing any challenge in molecular optoelectronics. However, this remains largely elusive because of the difficulties in its determination by conventional spectroscopic methods. This communication presents an in-device molecular spectroscopy (i-MOS) technique, which permits measuring this gap seamlessly, in real device operative conditions, at room temperature and without any previous knowledge of the material's parameters. This result is achieved by determining the occupied and unoccupied molecular orbitals of an organic semiconductor thin-film by using a single three terminal solid-state device.